Healthcare practices for users suffering from violence: from invisibility to comprehensive (un)care - Patrícia Caprini Guzzo; Marta Cocco da Costa; Ethel Bastos da Silva; Alice do Carmo Jahn
The aim of this study was to investigate practices of health professionals for users undergoing violence from perspective of comprehensive care. This study was based on a qualitative and descriptive research on graduate-level and technical health professionals who work in the Family Health Strategy programme in a northeastern municipality of Rio Grande do Sul. Data were collected by means of semi-structured interviews and analyzed using thematic mode. Results showed that these professionals do not utilize comprehensiveness to guide their care practices with users undergoing violence. Instead, they still work according to the biomedical model in which intervention is based on referring care to other sectors and the treatment plan. The study highlights the need for more appropriation and further discussion on practices regarding violence guided by the principle of comprehensiveness within the Family Healthcare team.